Incidental Findings in CT scan in Pediatric Populations with Head Injury - Ghimire, Prasanna; Paudel, Nabin; Koirala, Dwight (Journal of Nepalgunj Medical College, 2018)
Objective: To investigate the incidental findings in computed tomography scans performed for mild head injury in pediatric patients at Nepalgunj Medical College and Teaching Hospital, Kohalpur, Banke, Nepal. Materials and methods: It is a cross sectional hospital based study performed on two hundred and eighteen patients of age < 18 years presenting with mild head injury with no known neurological problem, recent surgery, and time of scanning < 24 hrs of sustaining injury were included in the study between Dec 2016 and June 2017. Results: Among the 218 patients, 134 were males and 84 females, age ranged from 3 months to 18 years. 196 out of 218 patients (89.9%) had incidental findings in CT scan images with greater than 2 incidental findings present in 54 patients. Sinus opacification was the most common incidental finding noted in 86 cases (43.9 %) followed by calcified granuloma in 27 cases (13.8 %). Incidental findings unrelated to trauma which required further investigation was present in 5 cases. Conclusion: Incidental findings are being increasingly encountered in computed tomography scan performed for mild head injury in pediatric age group with sinus opacification as the most common finding. Recognition of these findings and communication with the treating physician is helpful in the overall management of such cases.